Синтез, кристаллоструктурное и термическое исследование CzLiCrO4 - Клевцов, П. В.; Перепелица, Александр Петрович; Ищенко, Вера Николаевна; Клевцова, Р. Ф.; Глинская, Людмила Александровна; Круглик, А. И.; Александров, К. С. (My University, 1987)
Монокристаллы CzLiCrO4 получены испарением водного раствора простых хроматов цезия и лития. Выполнено детальное исследование структуры трех различных модификаций. Приведены кристаллографические и физико-химические характеристики CzLiCrO4. Monocrystals of CzLiCrO4 are preparated by evaporation of water solution of simple chromates cesium and lithium. Detal investigation of structure of three different modification is fulfilled. Crystallographycal and physic-chemical characteristics of CzLiCrO4 are showed.
Keywords: фазовые переходы; кристаллографические и физико-химические характеристики; три модификации; детальная структура; fase transitions; crystallographycal and physic-chemical characteristics; three modification; detal structure; кафедра харчової хімії